اليد العاملة الاجنبية وتحسين الأداء الوظيفي في المؤسسة الاقتصادية: عينة من المؤسسات الخاصة بولاية الوادي - محمد, جاب الله; داود, مسغوني; اسامة, موساوي (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة الى ابراز دور العمالة الأجنبية في تحسين الأداء الوظيفي في المؤسسة الاقتصادية في الجزائر، وقد تم اجراء دراسة تطبيقية على مجموعة من المؤسسات الاقتصادية الخاصة بالوادي والتي انتدبت عمال أجانب على مستواها: وهي مجمع التجاني الصناعي TPL، ومؤسسة روايال مونديال، ومؤسسة نجمة دقيق، ومؤسسة عويمر لصناعة الاعلاف. وقد اعتمد في الدراسة على المنهج الوصفي التحليلي في جمع البيانات والمعطيات المتعلقة بمتغيرات الدراسة، ولتحقيق هذا الهدف استخدم الاستبيان كأداة للدراسة وتم توزيعه داخل المؤسسات على عينة قدرها 45 عامل، واعتمد في تحليل مخرجات الاستبيان على برنامج الحزمة الإحصائية للعلوم الاجتماعية ((Spss. ولاختبار الفرضيات استخدمت المتوسطات الحسابية، الانحراف المعياري، اختبار تحليل التباين الأحادي، كما تم استخدام أساليب تحليل الانحدار والارتباط لإثبات وجود علاقة بين متغيرات الدراسة. وفي الاخير خلصت الدراسة إلى ان الدولة الجزائرية تعمل على ضبط حركة جلب العمالة الأجنبية، والعمل على حصرها في مجالات تحسين الأداء الوظيفي بالمؤسسات الاقتصادية. كما سجلت تباين في وجهات نظر العاملين في اهمية جلب العمالة الأجنبية. ""This study aims to highlight the important role of foreign work force in the improvement of the professional performance in the Private economic institution in EL OUED. Therefore, the researchers had made an applied study on a set of economic establishments in El-oued City, who foreign work force at their level. These establishments are Tedjani Industrial Complex TPL/ Mondial Royal Institution / Nadjma Dakik Institution. as well Awemer Institution for Fodder Manufacturing. The study adopted the descriptive and analytical methodology in collecting the database related to the study. Thus, we used the survey as a tool of study, and submitted to a sample of 45 laborers. Additionally, we adopted the Programme of Statistical Package for the Social Sciences (Spss) to analyze the survey's outlets. For analyzing the hypothesis, we used to prove the interrelaship among the variables of the study. In the end, the study concluded that the Algerian state is working to control the movement of foreign work, and work to limit it to the areas of improving job performance in economic institutions. It also recorded a discrepancy in the views of workers on the importance of bringing in foreign workers. "
مذكرة ماستر تجارة دولية
Keywords: اليد العاملة الأجنبية، الأداء الوظيفي، المؤسسة الاقتصادية، تحسين الأداء الوظيفي.; the foreign workforce, the professional performance, the economic institution. Job performance improvement.